2022
DOI: 10.3390/s22113991
|View full text |Cite
|
Sign up to set email alerts
|

Human Activity Recognition by Sequences of Skeleton Features

Abstract: In recent years, much effort has been devoted to the development of applications capable of detecting different types of human activity. In this field, fall detection is particularly relevant, especially for the elderly. On the one hand, some applications use wearable sensors that are integrated into cell phones, necklaces or smart bracelets to detect sudden movements of the person wearing the device. The main drawback of these types of systems is that these devices must be placed on a person’s body. This is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(44 citation statements)
references
References 51 publications
(68 reference statements)
1
43
0
Order By: Relevance
“…In the report of Gomez et al [ 25 ], they analyzed the evoked facial gestures in patients with 'Parkinson's Disease from the video of patients and indicated that the detection rate significantly improved (from 75.00% to 88.46%) by using the 17 facial features derived from the landmark detection algorithm. In addition, similar attempts have also been applied in the assessment of cerebral palsy [ 26 ], pose evaluation in sports [ 27 , 28 ], and human activity recognition [ 29 ]. The combination of pose estimation methods and machine learning classifiers presented superior performances in these works.…”
Section: Discussionmentioning
confidence: 99%
“…In the report of Gomez et al [ 25 ], they analyzed the evoked facial gestures in patients with 'Parkinson's Disease from the video of patients and indicated that the detection rate significantly improved (from 75.00% to 88.46%) by using the 17 facial features derived from the landmark detection algorithm. In addition, similar attempts have also been applied in the assessment of cerebral palsy [ 26 ], pose evaluation in sports [ 27 , 28 ], and human activity recognition [ 29 ]. The combination of pose estimation methods and machine learning classifiers presented superior performances in these works.…”
Section: Discussionmentioning
confidence: 99%
“…The current work is focused on detecting falls based on the overall movement of images in the scene. Pose estimation can be a potential future direction for this research [39]; however it is out of scope for the focus of this work. In future work, methods developed on this dataset can be applied on other public domain videos for further validation.…”
Section: Discussionmentioning
confidence: 99%
“…For example, H. Abdo et al [ 15 ] used RetinaNet to detect people in videos and obtain motion features and human shape features (including the aspect ratio of the human bounding box and motion history images), and then input the improved mobile nets to determine whether they fell or not; Y. Chen et al [ 16 ] used an OpenPose–SVM combination algorithm to detect people falling, which can accurately determine whether people tend to fall. The experiments proved that they achieved recognition rates of 92.5% and 95.8% on the two public data sets of MCFD and URFD, respectively; Ramirez et al [ 17 ] used the AlphaPose–kNN combination algorithm to detect people falling. First, AlphaPose was used to obtain the skeleton information of the human body; the information was then input into the kNN network for classification.…”
Section: Related Workmentioning
confidence: 99%